2020
DOI: 10.1002/eat.23266
|View full text |Cite
|
Sign up to set email alerts
|

What prevents young adults from seeking help? Barriers toward help‐seeking for eating disorder symptomatology

Abstract: Objectives: The aim of this study was to investigate help-seeking attitudes, intentions, and behaviors, and to systematically explore perceived barriers to help-seeking for eating, weight, or shape concerns among young adults. Differences in perceived barriers as a function of type of eating disorder symptomatology were also examined. Method: Data were collected using an online survey among individuals (aged 18-25 years) in Australia. Overall, 291 young adults with varying levels of eating disorder symptoms co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
78
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(89 citation statements)
references
References 76 publications
4
78
2
Order By: Relevance
“…This study identi ed several implications of exclusionary ED discourse and resultant shame and embarrassment for help-seeking. Consistent with previous ndings, this study indicated that many emerging adults have a preference for self-su ciency, with many deciding to deal with their di culties alone (15,(24)(25)(26)(27)35). This study identi ed that many emerging adults use self-help resources as a rst port of call.…”
Section: Phase 3: Feeling Excluded From Eating Disorder Discoursesupporting
confidence: 88%
See 1 more Smart Citation
“…This study identi ed several implications of exclusionary ED discourse and resultant shame and embarrassment for help-seeking. Consistent with previous ndings, this study indicated that many emerging adults have a preference for self-su ciency, with many deciding to deal with their di culties alone (15,(24)(25)(26)(27)35). This study identi ed that many emerging adults use self-help resources as a rst port of call.…”
Section: Phase 3: Feeling Excluded From Eating Disorder Discoursesupporting
confidence: 88%
“…A recent quantitative study was conducted in a community sample of Australian emerging adults with subclinical ED symptoms or past / current ED diagnosis or treatment. It identi ed denial and fear of change, stigma and self-su ciency as key barriers to ED help-seeking, providing further evidence that previously identi ed factors are also relevant to this life-stage (35). One qualitative study focused on a community sample of Asian American emerging adults with body image concerns and found that available resources and familial support were important facilitators of help-seeking.…”
mentioning
confidence: 91%
“…Improving healthcare professionals' knowledge at all levels is clearly key to achieving early diagnosis and intervention, but it is equally important to increase awareness among GPs of the clinical, particularly psychological, indicators of EDs [32]. Ali et al also suggested that help-seeking barriers may differ depending on the type of eating disorder symptomology [33]. The Internet may be useful in seeking help for bulimic EDs.…”
Section: Discussionmentioning
confidence: 99%
“…However, just two studies to our knowledge have explored barriers and facilitators of help-seeking for EDs during EA specifically. A recent quantitative study identified denial and fear of change, stigma and self-sufficiency as key barriers to ED help-seeking amongst Australian emerging adults, providing further evidence that previously identified factors are also this life-stage (35). Qualitative methodologies can complement such quantitative work by facilitating nuanced understandings of the complexity of help-seeking during this life-stage and generating hypotheses which might later be tested quantitatively.…”
Section: Introductionmentioning
confidence: 88%